2022
DOI: 10.20979/ueyd.1170268
|View full text |Cite
|
Sign up to set email alerts
|

Kurumsal Yönetimin Finansal Başarısında İç Kontrol Sisteminin Moderatör Etkisi

Abstract: An effective internal control system and the degree of compliance with corporate governance principles are important factors in ensuring the continuity of companies in capital markets. Financial performance is the most commonly used indicator for monitoring continuity. In the literature, there are studies investigating whether the internal control system and corporate governance principles have an effect on financial performance. However, there is no study investigating moderator effect of the internal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The demographic characteristics of the participants in the study were diverse. The majority of participants were male (58.4%), while 41.6% were female [1]. The age distribution showed that the largest age group was 25-34 years (31.6%), followed by 35-44 years (25.5%), 45-54 years (22.6%), and 55 years and above (20.3%) [2].…”
Section: Demographic Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The demographic characteristics of the participants in the study were diverse. The majority of participants were male (58.4%), while 41.6% were female [1]. The age distribution showed that the largest age group was 25-34 years (31.6%), followed by 35-44 years (25.5%), 45-54 years (22.6%), and 55 years and above (20.3%) [2].…”
Section: Demographic Samplementioning
confidence: 99%
“…The implementation and sustenance of strong internal control systems are crucial in preserving financial integrity and facilitating efficient corporate governance in today's business environment. Prior studies have demonstrated that internal control systems have a positive impact on both financial performance and technological innovation [1], [2]. The relevance of internal control systems in reducing financial fraud holds significant value, especially within the framework of increased financialization [3].…”
Section: Introductionmentioning
confidence: 99%